Non-Formal Education as a Discipline - Mina Harafah, Putri Julita; Setiawati, Setiawati (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
This article tries to explore the epistemology of science, ontology of science, and axiology of science. Looking at these three things, we try to present the epistemology of science, ontology of science, and axiology of science from the perspective of non-formal education. Pedagogical ontology examines the nature of education. Pedagogical epistemology is related to the source or origin of education, elements of education, educational methods, educational goals, etc. Meanwhile, the axiology of education examines the use value of education. The nature of education is a conscious effort to develop and guide the potential, personality, and basic skills of students towards personality and noble morals. The truth of education can be seen from the results or outcomes of the entire series of educational management based on the form of objects, systems, and methods, namely the form of intelligence, spiritual and emotional intelligence that exists in students.